2019
DOI: 10.1002/mar.21282
|View full text |Cite
|
Sign up to set email alerts
|

Cash, credit, or phone? An empirical study on the adoption of mobile payments in the United States

Abstract: The purpose of this study is to investigate the effects of consumer factors on behavioral intention to adopt mobile payments. We focus on the proximity mobile payment, which is made feasible by the near‐field communications (NFCs) technology. Building upon the theory of reasoned action and technology acceptance model (TAM), a behavioral intention model was established consisting of enhanced cognitive antecedents as well as affective and social antecedents. Cognitive antecedents encompass the factors including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 44 publications
(79 reference statements)
2
48
0
Order By: Relevance
“…While the intrusiveness of branded augmented reality face filter apps did not have negative effects on responses towards the app (Smink et al, 2019), the privacy concerns stemming from augmented reality face filters on social media decrease word‐of‐mouth and use intentions via perceived usefulness and flow, demonstrating different privacy concerns with this particular type of augmented reality. While other research investigating technology shows that privacy concerns affect perceived usefulness (Park et al, 2021) and still other research supports perceived usefulness as offering a relative advantage to a technology (J. Zhang & Mao, 2020), we document that this not only extends to augmented reality, but connect these effects through flow.…”
Section: Theoretical Contributionssupporting
confidence: 48%
See 1 more Smart Citation
“…While the intrusiveness of branded augmented reality face filter apps did not have negative effects on responses towards the app (Smink et al, 2019), the privacy concerns stemming from augmented reality face filters on social media decrease word‐of‐mouth and use intentions via perceived usefulness and flow, demonstrating different privacy concerns with this particular type of augmented reality. While other research investigating technology shows that privacy concerns affect perceived usefulness (Park et al, 2021) and still other research supports perceived usefulness as offering a relative advantage to a technology (J. Zhang & Mao, 2020), we document that this not only extends to augmented reality, but connect these effects through flow.…”
Section: Theoretical Contributionssupporting
confidence: 48%
“…Specifically, individual privacy perceptions increase the value attributed to a technology (Pizzi & Scarpi, 2020) and affect perceived usefulness (Park et al, 2021). Along these lines, when individuals anticipate benefits such as perceived usefulness, they perceive a relative advantage (J. Zhang & Mao, 2020), feeling more motivated to disclose their information and continue to use the technology (Benson et al, 2015; Hajli & Lin, 2016; X. Zhang et al, 2014). We contend that with heightened privacy concerns, individuals will see a technology as less useful for accomplishing a task, as it could pose a risk, and so would decrease use.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Technology acceptance model (TAM) theory has been used many times to help adopt new technology (Crittenden et al, 2020; Stern et al, 2008; Zhang & Mao, 2020). TAM theory has provided academics and managers with many useful insights about consumer behavior related to the personality's emotional and cognitive elements (Lin et al, 2007; Vahdat et al, 2020).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The extant m-payments literature confirmed that various research studies have been conducted in different countries; for example, USA (e.g. Zhang & Mao, 2020), UK , Germany (Gerpott & Meinert, 2017), Japan (Amoroso & Magnier-Watanabe, 2012), France (De Kerviler et al, 2016), China (Su et al, 2018;Zhou, 2014), Indonesia (Widodo et al, 2019), Malaysia (Lee et al, 2020;Leong et al, 2020;Tang et al, 2014), Oman (Sharma et al, 2018), India (e.g. ), Brazil (Ramos de Luna et al, 2016, South-Africa (Matemba & Li, 2018), and South Korea (Choi et al, 2020).…”
Section: Mobile Payment Adoption Researchmentioning
confidence: 74%
“…However, education and income did not play a significant role in predicting behavioral intentions. Building upon the theory of reasoned action (TRA) and TAM, Zhang and Mao (2020) investigated the effects of consumer factors on behavioral intention to adopt NFC m-payment. The results showed that relative advantage, attitude, and subjective norms significantly affected individual behavioral intentions.…”
Section: Mobile Payment Adoption Researchmentioning
confidence: 99%